공기업 CEO의 정치적 독립성, 이사회 의장 분리, 임원의 전문성과 성과 - 유승원 (13063, 2013)
Considering the relationship between state-owned enterprise (SOE) CEOs and political circles, this study examines the performance impacts of CEO’s succession type, board chair separation, and industry expertise and finance expertise of CEOs and outside d